Analisis Malware Ahmyth pada Platform Android Menggunakan Metode Reverse Engineering - Widiyasono, Nur; Mubarok, Husni; Fatwa MF, Agung (Generation Journal, 2022)
Android is the most widely used operating system in the world with a percentage of 74.82% in the Android operating system market share. This fact makes malicious software (malware) developers make mobile phone users with the Android operating system the main target for malware attacks. Attackers can change the application code by entering malicious code, repackaging the application, and publishing the application on the android application market. This study aims to find out how the malware that has been inserted into the android application works by using dynamic analysis and extracting the dangerous licenses used by the ahmyth malware by using reverse engineering techniques. The results of the analysis show that the ahmyth malware will run its service after the device restarts and waits for commands from the C&C server to perform certain actions on the infected device.